Effectiveness of Chest Pain Nursing Management on the Satisfaction of Patients with Angina in Emergency Unit - Albadry, Nora Hamed Abas; Hassen, Hakemia Shaker (Iraqi National Journal of Nursing Specialties, 2024)
Objective(s): to assess the effectiveness of chest pain nursing management on patients’ satisfaction with angina in the emergency unit.  Methods: A quasi-experimental study design was implemented in the emergency room of Al-Rifai General Hospital in Al-Nasiriya City, from December 9th, 2022 to June 18th, 2023. A non-probability (purposive) sampling of (100) patients who divided into two groups: the study group, which included (50) patients who received an urgent nursing intervention, and the control group included (50) patients who received routine urgent nursing intervention. The study used the Patient Satisfaction Nursing Care Quality Questionnaire, which included (17) questions. To determine the differences between the study and control groups, descriptive statistics (frequency, percentage, arithmetic mean, and standard deviations) and inferential statistics (Chi-square test and Independent T-test) were applied to the analysis of the data.Results: The research's findings demonstrated that there are substantial differences between the study group and the control group about pain severity, with the study group showing a decrease in pain severity when compared to the control group.Conclusion: The study concluded that chest pain nursing management was a suitable intervention. Compared to patients in the control group, patients were satisfied with prompt nurse assistance.Recommendations: The research suggested improving patient satisfaction, relieving or lessening pain intensity, and preventing complications, continue this nursing intervention by giving out booklets often to angina patients in the emergency room that provide guidelines for an optimal nurse response.